Islamic leardership principles as practiced by the principals of successful Islamic Schools in Riau, Indonesia - Bustami, Eka Nazra (Institute of Education, International Islamic University Malaysia, 2011)
Effective leadership in Islamic schools involves the incorporation of Islamic principles in the leadership behaviours and practices. The purpose of the study was to examine whether school principals in the selected successful Islamic schools exhibited and led their schools according to the principles of Islamic leadership. The study described leadership approaches used by school principals in Islamic schools and how those leadership approaches were influenced by Islamic leadership principles. In this attempt, the study compared the Islamic leadership principles derived from the literature with the leadership principles of principals of Islamic schools. Rich descriptive information about their leadership approaches, trait, and principles were obtained by individual and face-to-face interviews. The sample of the study was 10 successful Islamic school principals in the state of Riau province. It was found that all of the principals used the power-influence, trait-leaders, servant-leader, transformational, and situational approaches. Only seventy percent of the principals used the transactional leadership approach. The principals emphasized the importance of certain Islamic leadership principles, namely, conducting decision making process based on consultation; faith and belief in Allah (SWT); sharing vision and mission of their organization; maintaining the culture of the organization; putting the right people in the right place; building human relation; controlling change in order to achieve the stated objective; mobilizing the community; and providing space for constructive criticism. Based on the findings of the study, the researcher suggested that Department of Religious Affairs in Riau province release the schools' principals who are not qualified and certified. Then, they should provide them the opportunities to learn and grow by attending leadership courses and workshops. The researcher also suggested that a standard manual and guide line on responsibilities be prepared and assigned for both the principals and the school board members, so that, any tension and conflicts between them are avoided; and that a series of workshop on the knowledge and understanding of the Islamic law, Qur'an, Sunnah, and the Arabic language be conducted so that problems in this regard can be solved.